Іdentification of defects of the piles with reflected waves - Lebid, Oleksij; Kaliukh, Iurii; Berchun, Yaroslav; Chernyshev, Dmytro (ІТГІП, 2018)
Using current mathematical models of wave processes does not allow diagnosing defects in piles with sufficient accuracy. The necessity of creating of a pile generalized dynamic model which would allow to receive more reliable signals of wave processes in reinforced concrete piles has been substantiated. For numerical simulation of dynamic processes, a flat scheme for an axisymmetric pile based on the finite element method of "deep beam" within LIRA software complex was used. Sand was chosen as the soil around the pile due to the fact that sand and concrete characteristic impedance is very different, which provides a good echo from the pile toe (from the interface of the media). A comparative analysis of the results of mathematical modeling has made it possible to state that the most informative (in terms of differences in the comparison of graphs from one another), both for time signals and amplitude spectra, is the application of a horizontal impact on the lateral surface near the border with the pile base and the signal recording that comes to the speed sensors located in the vertical direction on the pile head near the border with the lateral surface. This option will be thoroughly tested numerically and experimentally in subsequent authors' studies.
Keywords: identification; defects; pile; reflected waves; numerical simulation